KOMBINASI INDIKATOR STATUS IODIUM PADA ANAK USIA SEKOLAH UNTUK MENILAI KESERIUSAN GANGGUAN AKIBAT KEKURANGAN IODIUM (COMBINED INDICATOR OF IODINE STATUS AMONG SCHOOL AGE CHILDREN TO ASSESS SEVERITY OF IODINE DEFICIENCY DISORDERS) - Mohamad Samsudin; Yuni Rahmawati; Ina Kusrini (Persagi, 2012)
ABSTRACT Iodine in salt fortification program is intended for universal iodized salt in the response to Iodine Deficiency Disorders (IDD). There are clinical indicators and biological indicators to assess the seriousness of the IDD problem among school-age children (SAC) is volume of the thyroid gland, urinary iodine concentration (UIC) levels, and levels of thyroglobulin (Tg). To assess the seriousness of IDD problem on the basis of the clinical and biological indicators of SAC. The study was conducted in Purbalingga, Pati and Malang Districts. Subjects were 10-12 years of age children. Data collected include UIC levels, Total Goiter Rate (TGR), and serum Tg levels. In Pati Districts: Wedarijaksa Subdistrict: median value of UIC was 150 µg/L; TGR was 28 percent and Tg >50 µg/L was 1 percent. Pucakwangi Subdistric: median value of UIC was 207 µg/L; TGR was 42 percent and Tg level >50 µg/L was 1,8 percent. In Purbalingga District: Karangtengah Subdistrict: median value of UIC was 191 µg/L; TGR was 11 percent and no children with Tg level >50 µg/L. Pengadegan: Subdistrict: median value of UIC was 232 µg/L; TGR was 8 percent and Tg level >50 µg/L was 1 percent. In Malang District: Sumber Manjing Wetan Subdistrict: median value of UIC was 148 µg/L; TGR was 1 percent and Tg level >50 µg/L was 2 percent. Poncokusumo Subdistrict: median value of UIC was 145 µg/L; TGR was 19 percent and no Tg level data. Seriousness of the IDD problem in Pati District: clinically is an area of endemic goiter, but biologically, iodine intake is sufficient. In Purbalingga District: clinically is an area of mild endemic goitre, but biologically, iodine intake is sufficient. In Malang Distrct: clinically is an area of non-endemic goiter and biologically, iodine intake is sufficient. Discrepancy between clinical indicators and biological indicators of iodine is the impact transition because of IDD control. Keywords: combined indicator, iodine status, school-age children, iodine deficiency ABSTRAK Program fortifikasi iodium dalam garam ditujukan untuk iodisasi garam universal dalam upaya penanggulangan masalah gangguan akibat kekurangan iodium (GAKI). Ada indikator klinis dan indikator biologis untuk menilai keseriusan masalah GAKI pada anak usia sekolah (AUS), yakni volume kelenjar tiroid, kadar ekskresi iodium urine (EIU), dan kadar tiroglobulin (Tg). Menilai keseriusan GAKI suatu daerah berdasarkan kombinasi indikator klinis dan biologis AUS. Penelitian dilaksanakan di Kabupaten Purbalingga, Pati dan Malang. Subjek adalah AUS 10-12 tahun. Data yang dikumpulkan meliputi kadar EIU, Total Goiter Rate (TGR), dan kadar Tg serum. Di Kabupaten Pati, di Kecamatan Wedarijaksa median EIU 150 µg/L, TGR 28 persen dan Tg >50µg/L 1 persen, sedangkan di Kecamatan Pucakwangi median EIU 207 µg/L, TGR 42 persen dan Tg >50µg/L 1,8 persen. Di Kabupaten Purbalingga, di Kecamatan Karangtengah median EIU 191 µg/L, TGR 11 persen dan Tg >50µg/L 0 persen, sedangkan di Kecamatan Pengadegan median EIU 232 µg/L, TGR 8 persen dan Tg >50µg/L 1 persen. Sementara di Kabupaten Malang, di Kecamatan Sumber Manjing Wetan median EIU 148 µg/L, TGR 1 persen dan Tg >50µg/L 2 persen, sedangkan di Kecamatan Poncokusumo median EIU 145 µg/L, TGR 19 persen dan Tg tidak ada. Keseriusan masalah GAKI di Kabupaten Pati secara klinis merupakan daerah gondok endemik, namun secara biologis, asupan iodiumnya sudah cukup. Kabupaten Purbalingga secara klinis merupakan daerah gondok endemik ringan, tetapi secara biologis, asupan iodiumnya juga sudah cukup. Kabupaten Malang secara klinis merupakan daerah non-endemik gondok dan secara biologis, asupan iodiumnya sudah cukup pula. Ketidaksesuaian antara indikator klinis dan biologis iodium merupakan dampak transisi dari upaya penanggulangan GAKI. [Penel Gizi Makan 2012, 35(2): 99-109] Kata kunci: kombinasi indikator, status iodium, anak usia sekolah, kekurangan iodium